Temporal variation of leaf nutrient retranslocation in exotic and indigenous tree species in Zagros forests, Iran - Mahnaz Karamian; Javad Mirzaei; Mehdi Heydari; Yahya Kooch; Daniel C.-F. S. Dey (Scientific Reports)
Abstract Plantations in degraded forest areas in arid and semi-arid regions play a vital role in restoring ecosystems, controlling erosion, and supporting local livelihoods. However, little is known about how exotic and native tree species influence nutrient dynamics in soil and foliage, particularly regarding nutrient retranslocation. This study evaluated seasonal variation in leaf nutrient concentrations and nutrient retranslocation patterns over a 6-month period (early April to late September) in 30-year-old plantations of two exotic needleleaf species (Cupressus arizonica, Pinus eldarica) and two indigenous broadleaf species (Amygdalus scoparia, Quercus brantii). The findings revealed significant differences among species groups. Broadleaf species generally exhibited higher concentrations of leaf nutrients (such as nitrogen (N), phosphorus (P), potassium (K), and magnesium (Mg) and lower C: N ratios than needleleaf species. Seasonal effects were evident, with leaf nutrient content generally higher in spring than in summer. The order of nutrient retranslocation was as follows: Ca < C < K < Mg < N < P. Further analysis using principal components highlighted the differences between broadleaf and needleleaf plantations in terms of soil and leaf nutrient status. These findings suggest that, due to its native status and greater contribution to soil fertility, Q. brantii is a suitable choice for reforestation in similarly degraded environments.